Assumptions for the strategy for conservation and management of wisent population in Augustowska Forest (European Bison Conservation Newsletter, 2021)
Reintroduction of European bison to Augustowska Forest is a part of restitution of this species to its natural range in north-eastern Europe. The capacity of this forest complex of about 115 thousand ha, was estimated for about 40 individuals. Initial group of animals introduced there in 2018 counted 7 wisents, by the end of 2019 it grew up to 9 individuals. In 2020, 4 additional animals were brought there and with one calf born that spring the whole population counted 14 individuals by June 2020. Assumed target population numbers should be reached there in 10 to 15 years. Suggested are measures regarding an improvement of local habitats, population management and regulation of its numbers, prevention of damages in agriculture and other human related conflicts, monitoring of wisent population and habitats within its home range. Identified threats for this population are mostly of anthropogenic origin.
Keywords: wisent; population; conservation; management; Augustowska Forest